2020
DOI: 10.1111/jan.14531
|View full text |Cite
|
Sign up to set email alerts
|

Nursing students’ resilience, depression, well‐being, and academic distress: Testing a moderated mediation model

Abstract: Aim Academic distress is a leading cause of attrition among nursing students. The present study tested a positive psychology‐oriented model detailing the potential links between nursing students’: (a) psychological resilience; (b) depressive symptoms; (c) intrapersonal well‐being; (d) interpersonal well‐being; and (e) academic distress. Additionally, we tested whether the academic benefits of resilience were conditional upon nursing students’ perceptions of their campus climate as supportive of mental health a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
44
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(59 citation statements)
references
References 50 publications
1
44
0
Order By: Relevance
“…Both quantitative and qualitative studies have described U.S. nursing student experiences during this abrupt transition as traumatic, stressful, and filled with fear, uncertainty, loneliness, and missed opportunity ( Diaz et al, 2021 ; Fitzgerald & Konrad, 2021 ; Goddard et al, 2021 ; Kim et al, 2021 ; Michel et al, 2021 ). The presence of depressive symptoms in nursing students was well-documented before the COVID-19 pandemic ( McDermott et al, 2020 ; Tung et al, 2018 ). Kim et al (2021) found a three-fold increase in nursing student depression measures during the early months of the COVID-19 pandemic compared to pre-pandemic levels.…”
Section: Review Of the Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…Both quantitative and qualitative studies have described U.S. nursing student experiences during this abrupt transition as traumatic, stressful, and filled with fear, uncertainty, loneliness, and missed opportunity ( Diaz et al, 2021 ; Fitzgerald & Konrad, 2021 ; Goddard et al, 2021 ; Kim et al, 2021 ; Michel et al, 2021 ). The presence of depressive symptoms in nursing students was well-documented before the COVID-19 pandemic ( McDermott et al, 2020 ; Tung et al, 2018 ). Kim et al (2021) found a three-fold increase in nursing student depression measures during the early months of the COVID-19 pandemic compared to pre-pandemic levels.…”
Section: Review Of the Literaturementioning
confidence: 99%
“…The correlation between stress and depression in nursing students is well documented ( De Gagne et al, 2021 ; Finley, 2020 ; McDermott et al, 2020 ; Park et al, 2019 ). Nursing students tend to be older, married, and are more likely to have family commitments outside the classroom than college students in non-nursing majors.…”
Section: Review Of the Literaturementioning
confidence: 99%
“…It enables people to thrive under challenging or threatening circumstances [10]. College students with high resilience tend to more actively mobilize internal and external resources to tackle the adversity, and they are less likely to have mental health problems, poor academic performance, and interpersonal problems compared to those with low resilience [11,12]. Given the great significance of resilience for college students, how to promote their resilience merits greater attention.…”
Section: Introductionmentioning
confidence: 99%
“…Resilience, like grit, is a significant value crucial to the development of nursing education (Meyer et al, 2020). School administrators and nurse educators alike should create a milieu where resilience is nurtured, thus decreasing the unwanted impact of stress and anxiety among students, leading to their optimal well-being and ideal state of mind and body suitable for learning (McDermott et al, 2020). Accordingly, the American Holistic Nurses Association (AHNA, 2021) advocates a treatment approach that relies on the outcomes of evidence-based research on holistic treatment methods.…”
Section: Introductionmentioning
confidence: 99%
“…Fowler et al (2020) also found that resilience can develop among nursing students throughout the years during their nursing schooling. Therefore, it only shows that the academic environment has an obligation to foster resilience and develop this trait among the students (Cam, 2017;Li & Hasson, 2020;Mcdermott et al, 2020;Ramalisa et al, 2018;Rios-Risquez et al, 2016). Since resilience is a trait to be lived with by nursing students, it has to be taught and developed in them (Taylor et al, 2020).…”
Section: Introductionmentioning
confidence: 99%